Teaching early reading & phonics creative approaches to early literacy - Goouch, Kathy; Lambirth, Andrew (SAGE, 2017)
Learning to read is an exciting and vital part of every child's development. The new edition of this book continues to provide trainees and teachers with a broad understanding of teaching reading & phonics, and equip them with the skills necessary to face the reality of the early years classroom in order to meet the needs of individual children. With vital information on constructing relationships with the young readers, and how to plan phonics within a rich, interactive and playful literacy pedagogy, the second edition now includes: a brand new chapter on babies and early reading; more information on language acquisition and how children learn; a discussion of children with SEN; an appreciation for the rise of digital technologies in relation to reading; whether you're training to become a teacher, or already working in the classroom this book is ideal for those who wish embed the teaching of phonics into carefully selected high quality materials - particularly in children's literature.--Provided by publisher.